1998
DOI: 10.1021/om980444s
|View full text |Cite
|
Sign up to set email alerts
|

Physical Organic Chemistry of Transition Metal Carbene Complexes. 13.1 Kinetics of Proton Transfer from (5-Methyl-2-oxacyclopentylidene)pentacarbonylchromium(0) and Hydrolysis of Its Conjugate Anion in Aqueous Acetonitrile

Abstract: The pK a = 13.41 of the title compound (5), determined by a kinetic method, is about 1.3 units lower than the pK a of (2-oxacyclopentylidene)pentacarbonylchromium(0) (1) in 50% MeCN−50% water at 25 °C. The acidifying effect of the methyl group is attributed to its stabilizing effect on the CC double-bond resonance structure of the anion (5 - ). The rate constant for deprotonation of 5 by OH- is about the same as for deprotonation of 1, despite the higher acidity of 5. This means that the intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 22 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…The mechanisms of hydrolysis of Fischer carbene complexes have been extensively studied by the group of Bernasconi . Kinetic studies carried out with carbene complexes with ionizable α-carbons 525 , 526 , 527 , 528 , 529 , and 530 revealed that the hydrolysis (50% MeCN−50% water) is pH dependent (a general base-catalyzed reaction) and is subject to a substantial kinetic solvent isotope effect ( k H2O / k D2O ) larger in magnitude as the pH of the medium increases, which is consistent with a rate-limiting proton transfer (Figure ).…”
Section: Reactions Of Metal−carbene Complexesmentioning
confidence: 92%
“…The mechanisms of hydrolysis of Fischer carbene complexes have been extensively studied by the group of Bernasconi . Kinetic studies carried out with carbene complexes with ionizable α-carbons 525 , 526 , 527 , 528 , 529 , and 530 revealed that the hydrolysis (50% MeCN−50% water) is pH dependent (a general base-catalyzed reaction) and is subject to a substantial kinetic solvent isotope effect ( k H2O / k D2O ) larger in magnitude as the pH of the medium increases, which is consistent with a rate-limiting proton transfer (Figure ).…”
Section: Reactions Of Metal−carbene Complexesmentioning
confidence: 92%
“…Over the past decade, we have reported a number of kinetic and thermodynamic investigations of the reversible deprotonation of Fischer carbene complexes. Most of the complexes studied were of the type 1H where M is Cr or W; CH 3 X with X = O or S acts as a π-donor, while R and R‘ are H, alkyl, or aryl groups. The majority of the studies were performed in 50% MeCN−50% water (v/v) at 25 °C; , one investigation was carried out in water, another one in pure acetonitrile, and one in various MeCN−water mixtures . The most important findings can be summarized as follows.…”
Section: Introductionmentioning
confidence: 99%
“…Very little additional quantitative work on acidities was performed until 1989, when we published the first kinetic proton-transfer study on a Fischer carbene complex ( 2 -Cr) , Most of these data have been obtained in 50% MeCN−50% water, a solvent chosen because it is essentially aqueous but allows the carbene complexes to be soluble enough for such determinations. Virtually all carbene complexes investigated so far are of the general structure 1 -M where M = Cr, W, and, in one case, Mo; R was either Me or Et while R‘ and R‘ ‘ included H, Me, n -Pr, and Ph.…”
Section: Introductionmentioning
confidence: 99%